Separación de microplásticos mediante procesos físico-químicos en aguas residuales en la ciudad de Riobamba - Barros Barreno, Wilson Adrián (2021)
Microplastics are small particles smaller than 5 mm, originating from the degradation of single- use products, they transported by means of wastewater, which, as they are not retained in the treatment processes, transferred to different aquatic organisms causing potential damage to the human beings. The research is exploratory and experimental because it aims to analyze the separation of microplastics by density through the application of physicochemical processes in wastewater collected from the public discharges of the sewerage system of Riobamba city. The measurement of initial parameters used with 4 samples of wastewater measuring turbidity, electrical conductivity, total dissolved solids and ph. Subsequently, the existence of microplastics in each sample identified, for a better verification a gram of degraded plastic added, dissolved in 1 liter of sample. Finally, reagents (Zinc Chloride, Sodium Iodide, Sodium Politungstate) used to achieve a separation of the liquid obtaining new values in the measured parameters. The results obtained affirm that by means of the density separation method a better efficiency is achieved using zinc chloride in a concentration of 0.5g dissolved in 100 ml of distilled water and added to 1 liter of waste water sample, obtaining an efficiency of 87.22% and retention of microplastics of 63.49%.